Dealing With the Pain. - Bono, Agostino (America Magazine: The Jesuit Review of Faith & Culture, 2003)
Reports on the outreach program of Catholic bishops in the U.S. aimed at dealing with the human pain of victims of sexual abuse of minors by members of the clergy. Role of bishops' Charter for the Protection of Children and Young People in the church's pastoral outreach efforts; Importance of the meeting between bishops and victims for the healing process; Comments from Michael Bland, clinical psychologist and member of the bishops' National Review Board.